Classification of the nullity for the second order discrete nonlocal problems - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2014)
In this paper we investigate the nullity of second order discrete problem with two nonlocal conditions. The classification of nullity with respect to rows and columns of discrete problem matrix is presented. The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/2014).